Ultrasonography in Gastroenterology: The Need for Training - Pinto,João (2018)
The use of ultrasonography (US) as an imaging modality in medicine has spread across almost every clinical specialty. This diffusion is based on the simplicity, accessibility, portability and affordability of the technique producing real-time high-resolution images using non-ionising radiation. On the other hand, this trend also extended the technique to settings other than healthcare, such as public facilities, private houses or remote sites. This tendency can be observed worldwide, from developing countries to prestigious medical schools and tertiary referral hospitals. Furthermore, point-of-care US (POCUS), i.e., US executed at the patients bedside to obtain real-time objective information with diagnostic and clinical monitoring purposes or to guide invasive procedures, has been incorporated in many specialties. In gastroenterology, despite the essential role of endoscopy, clinical practice is highly dependent on non-endoscopic imaging techniques. However, as in other specialties, the indications of US in gastroenterology have been increasing steadily, covering a broad range of conditions. In response to the generalised employment of US by non-radiologists, institutions such as the European Federation of Societies for Ultrasound in Medicine and Biology and the Royal College of Radiologists issued recommendations to ensure high-quality practice. These theoretical and practical requisites include performing a certain number of examinations and mandatory skills in order to achieve certification to execute unsupervised US. Therefore, there is a need for modern gastroenterology to include US as a basic skill in its clinical practice. To ensure the provision of high-quality US, adequate instruction of future specialists should be guaranteed by the gastroenterology departments and required in the residency training programme.